Literasi Keuangan, Efikasi Keuangan dan Pendapatan Terhadap Keputusan Investasi di Masa Covid-19 Pada Masyarakat Kota Jambi - Heriyani, Heriyani; Rusfa, Dilla Dwi Rahmatin; Rismayati, Indri (Sosio e-Kons, 2023)
The development of economic growth in the era of globalization in Indonesia is currently experiencing very rapid progress. Therefore every individual or everyone must have sufficient knowledge and ability to manage a financial resource. This study aims to determine the effect of financial literacy, financial efficacy, and income on investment decisions during the Covid-19 period in the people of Jambi City. The sampling technique is using a purposive sampling method by distributing questionnaires as an instrument for taking a sample of 100 respondents. Researchers use a quantitative and associative approach. This study uses Multiple Linear Analysis namely T Test and F Test with data processing using SPSS 25 Software. The results of this study indicate that: (1) Financial literacy has a significant effect on investment decisions (2) Financial efficacy has no significant effect on investment decisions (3) Income has a significant effect on investment decisions and (4) Financial literacy, financial efficacy and income together have an effect on investment decisions. The results of the R2 test show that the variables financial literacy, financial efficacy, and income, and risk explain 68.9% of the dependent variable, namely investment decisions, while the remaining 31.1% is explained by other variables not included in this study.